Astrocyte identity: Evolutionary perspectives on astrocyte functions and heterogeneity - Yang, Yongjie (Curr Opin Neurobiol, 2018)
The development of new animal models, in vivo isolation approaches, and improvements in genome-wide RNA expression methods have greatly propelled molecular profiling of astrocytes and the characterization of astrocyte heterogeneity in the central nervous system (CNS). Several recent reviews have comprehensively discussed the molecular and functional diversity of mammalian astrocytes. In this brief review, we emphasize interspecies comparisons and an evolutionary perspective regarding the astro(glia) of vertebrates and invertebrates which are similar in form and function. This analysis has revealed conserved astrocyte transcriptomes in the fly, mouse and human. We also offer opinions about the pattern and origin of astrocyte heterogeneity in the CNS.